Analisis Jabatan Fungsional Pengelola Pengadaan Barangjasa pada Lingkungan Pemerintah - Ningrum, Siti Kartinah; Herdiansyah, Muhammad Izman (Universitas Bunda Mulia, 2024)
The purpose to be achieved in this study is to determine and analyze the implementation of the achievement of the functional position of goods and services procurement manager in the environment of South Sumatra Province. Key informants in this study were 7 people consisting of 5 Functional Officials of Goods and Services Procurement Managers and 2 structural officials. The analysis technique used is descriptive qualitative. The research results show that fulfilling the needs of the Functional Position of Goods and Services Procurement Manager has been supported by a good communication process, where changes in rules occur within a short period of time, thereby confusing the employees who are participants in the program. Apart from that, it has also been supported by reliable resources who have expertise in their fields, have a clear and measurable implementation time of 12 months and the availability of adequate facilities and infrastructure, for example computer facilities connected to the internet, printers and adequate space. In the disposition aspect, implementors and participants understand the aims and objectives of the policy program, especially implementation that prioritizes a sense of justice. Another factor is the bureaucratic structure that supports supervision and support from the executive and legislative parties.